The Impact of Market Liquidity on the Effectiveness of Option Valuation with the Black-Scholes-Merton Model Using the Example of the WIG20 Index - Prymon, Michał (Wpływ płynności na efektywność wyceny opcji modelem Blacka-Scholesa-Mertona na przykładzie indeksu WIG20, 2022)
The Black-Scholes-Merton model is one of the most popular option pricing models used in market practice. This model is based on unrealistic assumptions, including the lack of transaction costs. While it is not possible to satisfy all the conditions of the model, it is logical to assume that perfectly liquid markets will meet them better, which will help to reduce the risk of error. The aim of the article was to measure the impact of liquidity to the divergence of the Black-Scholes-Merton model compared to real market closing prices. The result of the research demonstrates a moderate dependence between the volume of the WIG20 index, the volume of option transactions and a negative correlation with the ILLIQ illiquidity indicator introduced by Amihud (2002). The research led to the conclusion that there is a positive correlation between the liquidity and the divergence between BSM model and the market prices.
Financial Sciences. Nauki o Finansach, 2022, vol. 27, no. 1, s. 58-68
Keywords: options; Warsaw Stock Exchange; WIG20; Black-Scholes-Merton (models); pricing models; derivatives; index options; opcje; GPW; model Blacka-Scholesa-Mertona; modele wyceny; instrumenty pochodne